Analysis of Added Value of Crab Crab Processing Business at Home Industry MP KDK 1 in Tapi-But Village Marrobo District, Muna Regency - Andi gamu; Sarinah Sarinah; Sakir Sakir (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
This study aims to determine the stages of processing crab crabs in the Home Industry of MP KDK 1 in Tapi-But Village, Muna Regency, by using added value analysis, namely the Hayami Method, which shows the crab production industry. Based on the study results through 4 stages of processing, namely steaming, separating shells and claws, packaging, and cooling. The added value created from processed crab activities is IDR 30,748, while the added value created for one month is IDR 90,337,624.